ADAPTABILITAS, PERTUMBUHAN DAN REGENERASI PADA PLOT KONSERVASI EX SITU MERBAU - Tri Pamungkas Yudhohartono; Burhan Ismail (Jurnal Pemuliaan Tanaman Hutan, 2013)
Merbau is one of threatened forest genetic resources. Based on IUCN Red List Categories. conservation status of merbau is vulnerable (VU A1cd). Conservation effort of merbau is urgently required to save this species from extinction. Center for Forest Biotechnology and Tree Improvement Yogyakarta had established ex situ conservation plots of merbau in Forest Research in Bondowoso, East Java and Gunung Kidul Yogyakarta. Genetic resources used in those ex situ conservation plots were from seven provenances namely Halmahera Timur, Waigo, Oransbari, Wasior, Nabire, Seram, dan Mandopi/Twanwawi. This research aims to evaluate adaptability, growth and regeneration of merbau plants grown in ex situ conservation plots in Bondowoso dan Gunung Kidul. The ex situ conservation plot in Bondowoso was designed as Randomized Complete Block Design with single factor of provenance. At the ex situ conservation plot in Gunung Kidul each provenance was planted in one block. The results showed that adaptability of merbau plants at ex situ conservation plots in Bondowoso dan Gunung Kidul was good. Growth of height and diameter of merbau plants from several provenances at ex situ conservation plot in Gunung Kidul were better than those in Bondowoso at all observation ages. Height and diameter average of merbau plants at ex situ conservation plots in Bondowoso and Gunung Kidul at one year old were 78.21 cm; 9.58 mm and 97.88 cm; 9.58 mm respectively. Height and diameter average of merbau plants at ex situ conservation plots in Bondowoso and Gunung Kidul at two years old were 95.36 cm; 12.95 mm and cm; 19.62 mm respectively. Regeneration of merbau has been successful at Gunung Kidul  plot. Some of the fallen seeds were then grown  to be wildlings. Whereas, regeneration of merbau at  ex situ conservation plot in Bondowoso was regarded as not successful